Bridging Cultures Through Music: A Stylistic and Cross-Cultural Analysis of Figurative Language Translation in C-Pop - Siregar, Sheyra Silvia; Siregar, Sheyla Silvia (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2025)
This study explores how figurative language in WayV’s Kick Back (秘境) album functions stylistically and how its meanings are transferred through translation for cross-cultural audiences. Music serves as a medium that bridges cultural boundaries, and the translation of figurative expressions plays a crucial role in shaping intercultural understanding. Using a descriptive qualitative approach, this research analyzes figurative devices found in three selected song lyrics through listening and note-taking techniques. Data were processed using the Miles and Huberman interactive model, while semantic validation, expert judgment, and intrarater reliability ensured data credibility. The analysis identifies seven types of figurative language: simile (12 instances), personification (2), metonymy/synecdoche (1), nianlian (1), parallelism (1), contrast (2), and rhetorical question (1). Connotative meaning dominates the figurative expressions. Simile emerges as the most frequent stylistic device. The findings show that figurative language not only shapes the emotional and aesthetic tone of the songs but also presents challenges in translation, particularly in maintaining stylistic effect and cultural nuance. This study highlights how stylistic translation contributes to cross-cultural communication by enabling listeners from different linguistic backgrounds to access the intended meanings embedded in the lyrics.